The safety and use of perioperative dexamethasone in the perioperative management of primary sporadic supratentorial meningiomas - Arlt, Felix; Basaran, Alim Emre; Vogel, Markus; Vychopen, Martin; Seidel, Clemens; Barrantes-Freer, Alonso; Güresir, Erdem; Wach, Johannes (Frontiers in Oncology, 2024)
Objective Despite the lack of prospective evidence for the perioperative use of dexamethasone in meningioma surgery, its use is well established in the daily routine of several centers. The present study evaluates the effect of dexamethasone on postoperative complications, peritumoral T2/FLAIR hyperintensity, and progression-free survival in patients with supratentorial meningiomas undergoing resection. Methods A total of 148 patients who underwent resection of a primary sporadic supratentorial meningioma at the authors’ institution between 2018 and 2020 were included in this retrospective cohort. Safety criteria were side effects of dexamethasone (e.g. hyperglycemia), surgical morbidities, length of stay, and mortality. The individual Karnofsky Performance Scales (KPS) were evaluated regarding the individual development and the delta of KPS at 3- and 12-months compared to baseline KPS was calculated. Longitudinal assessment of the peritumoral T2-/FLAIR hyperintensity changes was performed. Results The use of both pre- and postoperative dexamethasone did not influence the incidence rates of wound infections, infarctions, postoperative seizures, pulmonary embolism, postoperative hemorrhage, mortality, length of stay, new-onset hyperglycemia and new neurological deficits. Perioperative Dexamethasone use was associated with an improved Karnofsky performance development at 3- (delta of KPS 3.3 vs. -1.9, p=0.001) and 12-months (delta of KPS 3.8 vs. -1.1, p=0.008) compared to the preoperative Karnofsky performance status. Multivariable analysis revealed that perioperative dexamethasone use enhances the KPS improvement (OR: 3.65, 95% CI: 1.01-13.18, p=0.048). Persistent peritumoral T2/FLAIR hyperintensity changes were observed in 35 cases of 70 patients with available follow-up images and a baseline edema (50.0%). Perioperative dexamethasone use enhanced the reduction of the preoperative peritumoral T2-/FLAIR hyperintensity changes (mean reduction of maximum diameter: 1.8 cm vs. 1.1 cm, p=0.023). Perioperative dexamethasone use was independently associated with a lower risk for persistent peritumoral T2-/FLAIR hyperintensity changes (OR: 3.77, 95% CI: 1.05-13.54, p=0.042) The perioperative use of dexamethasone did not influence the progression-free survival time in Simpson grade I or II resected WHO grade 1 meningiomas (log-rank test: p=0.27). Conclusion Perioperative dexamethasone use seems to be safe in surgery for primary supratentorial meningiomas. Dexamethasone use might enhance the functionality by reducing postoperative peritumoral T2-/FLAIR hyperintensities. These findings highlight the need for prospective data.